Verifying the application of the HACCP requirements in some food factories in the Eastern Province of the Kingdom of Saudi Arabia - Aljalisi, Turki Abdullah; Madkour, Mohamed Hussein; Abd El-Razik, Mohamed Moustafa (Journal of agricultural, environmental and veterinary sciences, 2021)
This research aims to verify the effective application of the HACCP system in some food factories in the Kingdom of Saudi Arabia and to suggest ways to increase the effectiveness of the application to ensure the safety of food products, as the extent to which food factories adhere to the application of good manufacturing practices as well as the effectiveness of applying the HACCP system will be evaluated. Critical (HACCP), by using an examination to assess the extent of compliance of food establishments, the study urges good manufacturing requirements as well as the correct application design of the HACCP system, in addition to working on linking the results of laboratory analyzes of samples of food products that were withdrawn from the food establishments under study with the actual reality of manufacturing practices Good and effective application of the HACCP system, The research was conducted on a sample consisting of (100) food factories located in the eastern region, randomly selected in order to verify the extent of their compliance with the requirements of good manufacturing and the standard specifications and technical regulations, by conducting field visits to the factories that were studied. The data were also processed statistically through the Statistical Package for Social Sciences program, where the results of the study indicated that the majority of the food factories under study were good and high technical requirements, especially in industrial areas, Where the percentage of application of technical requirements in the final product and storage warehouses was excellent, and the percentage of application of the requirements ranged between (87-92%), raw materials warehouses ranged between (69-81%), and the production department ranged between (78-91%).And the researcher provided appropriate recommendations and solutions, including continuous checking and reviewing the application of the HACCP system and making the HACCP system mandatory for all food factories.